Psychosocial Aspects of the Work of Female Call Center Operators in a Bank of São Paulo, Brazil - Raab, Débora Miriam; Rocha, Lys Esther (Psykhe, 2002)
The objective of this study was to identify psychosocial aspects of the working conditions of female call center operators from a bank in São Paulo, Brazil. The aim was not only to identify these factors, but also to understand why they ocurred and how they were processed. The methods included Ergonomic Work Analysis, composed of systematic observations of work, interviews and document analysis. Self-administered questionnaires were responded by 109 call center operators, of which 96 (88.1%) were female, and 76 (70.4%) of them aged from 18 to 23 The psychosocial aspects identified in the working conditions of these female operators included: high quantitative and qualitative demands, with significant emotional, cognitive and physical loads; lack of control over work; the volume of information to be dealt with; contradictory demands from the enterprise for higher productivity based on average work time and service quality; difficult relationships with customers; pœssure from queues during some periods; and the contrast between the monotony and complexity of the task.